Second time around - Carlson, Melody (Revell, a division of Baker Publishing Group, 2023)
"When empty-nester Marley Farrell inherits a rundown tourist shop, she never expects to rediscover her love for the funky coastal Oregon town -- or her now-widowed teenage crush. With his help, she may just be able to renovate the shabby shop -- and her lackluster love life" --